Civil Engineering and Disaster Prevention PROCEEDINGS OF THE 4TH INTERNATIONAL CONFERENCE ON CIVIL, ARCHITECTURE AND DISASTER PREVENTION AND CONTROL (CADPC 2023), SUZHOU, CHINA, 24-26 MARCH 2023 - Zende, Abhijit Mohanrao; Ren, Xin; Gao, Qingfei (CRC Press, 2024)
Civil Engineering and Disaster Prevention focuses on the research of civil engineering, architecture and disaster prevention and control. These proceedings gather the most cutting-edge research and achievements, aiming to provide scholars and engineers with valuable research direction and engineering solutions. Subjects covered in the proceedings include: civil engineering, engineering structure, architectural materials, disaster prevention and control, and building electrical engineering. The works of these proceedings aim to promote the development of civil engineering and environment engineering. Thereby, fostering scientific information interchange between scholars from the top universities, research centers and high-tech enterprises working all around the world.